2020
DOI: 10.1002/ese3.600
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase flow behavior in deep water drilling: The influence of gas hydrate

Abstract: Hydrate phase transition may bring hidden dangers for well control safety, even accidents of blowout happen in deep water drilling. Accurate calculation of all the drilling parameters is of great importance for well control safety. In this study, the mathematic models of transient heat transfer and multiphase flow have been established with the consideration of hydrate phase transition. Furthermore, the position where hydrate formation is most likely to occur was predicted with the proposed models, and the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…For the multi-phase pipe flow, the friction coefficient calculation formulae vary with the flow pattern. 39 When the gas and water phases are in a critical liquid removal state, the flow pattern in the wellbore is an annular mist flow. 40 Yu Xichong 41 suggested that the calculation method for the friction coefficient of monophasic flow could be applied to obtain the friction coefficient between the fluid and pipe wall in a multi-phase pipe flow, including stratified, annular, and slug flows.…”
Section: F I G U R E 3 Comparison Between Results Obtained By Different Drag Coefficient Models and Laboratory Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For the multi-phase pipe flow, the friction coefficient calculation formulae vary with the flow pattern. 39 When the gas and water phases are in a critical liquid removal state, the flow pattern in the wellbore is an annular mist flow. 40 Yu Xichong 41 suggested that the calculation method for the friction coefficient of monophasic flow could be applied to obtain the friction coefficient between the fluid and pipe wall in a multi-phase pipe flow, including stratified, annular, and slug flows.…”
Section: F I G U R E 3 Comparison Between Results Obtained By Different Drag Coefficient Models and Laboratory Datamentioning
confidence: 99%
“…Equation () indicates that the friction coefficient of the gas‐liquid two‐phase pipe flow is required in the calculation of the critical droplet entrainment rate. For the multi‐phase pipe flow, the friction coefficient calculation formulae vary with the flow pattern 39 . When the gas and water phases are in a critical liquid removal state, the flow pattern in the wellbore is an annular mist flow 40 .…”
Section: New Entrained Droplet Modelmentioning
confidence: 99%
“…The exploration process faces serious drilling risks caused by the deep-water environment. Due to the appropriate temperature and pressure which meet the conditions for gas hydrate formation in deep-water oil and gas exploitation, gas hydrate formation in drilling pipelines has been a major problem which strictly restricts the safe and efficient exploitation of deep-water oil and gas. …”
Section: Introductionmentioning
confidence: 99%
“…In view of increasingly stringent environmental protection rules, water-based drilling fluids have been gradually used instead of oil-based drilling fluids during oil and gas exploitation. This may increase the possibility of hydrate formation in the drilling fluid. ,,, When drilling in deep-water fields, free gas may invade the wellbore annulus. As the gas and drilling fluids flow in the annulus, gas hydrates may continue to form and accumulate under appropriate temperature and pressure conditions, as seen in Figure , which leads to changes in the drilling fluid’s performance and interruption of the normal drilling operation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation